Randomized double-blind comparison of remifentanil and alfentanil in patients undergoing laparoscopic cholecystectomy using total intravenous anesthesia - José M Belena; Mónica Núñez; Alfonso Vidal; Diego Anta (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: To compare the use of remifentanil and alfentanil to suppress intraoperative adrenergic response of pain and the influence of these drugs on the recovery profile in patients undergoing laparoscopic cholecystectomy using a total intravenous anesthesia (TIVA) technique. Material and Methods: One hundred patients undergoing elective laparoscopic cholecystectomy were randomized to be managed with either remifentanil (group R) or alfentanil (group A). During general anesthesia, we evaluated adrenergic responses to intubation to first surgical incision and over the surgical procedure. We also recorded time to first spontaneous breathing, time to successful ventilation, time to respond to verbal orders, and time to extubation. Results: The R group reported a significantly lower number of responses to intubation and responses to first surgical incision (14% vs. 30%; P = 0.013 and 8% vs. 18%; P = 0,037, respectively). The event of one or more responses during the surgical procedure was also lower in the R group (56% vs. 70%; P = 0.017). Hypertensive response to surgical stimuli during the procedure was lower in the R group as well as a lower frequency of tachycardia episodes in this group (34% vs. 56%; P = 0.033 and 28% vs. 44%; P = 0.041, respectively). No differences were found between groups relating to the percentage of hypotensive episodes and no episodes of bradycardia were appreciated. Both groups were similar relating to recovery times: time to the first spontaneous breathing, time to successful ventilation, time to respond to verbal orders, and time to extubation. Conclusion: Remifentanil showed a more stable hemodynamic response during the surgery compared with the use of alfentanil in anesthetized patients undergoing laparoscopic cholecystectomy using TIVA. Both opioids, alfentanil and remifentanil, have a similar recovery profile, and they do not delay time to awakening.